Obesity Prevalence Through Diet and Physical Activity in Medical Faculty Students - Ago Harlim; Yoggy Adhitya Nusantara (Universitas Aisyah Pringsewu, 2022)
This study aimed to determine the description of the diet and physical activity in students of the Faculty of Medicine related to obesity. This type of research is descriptive research with the cross-sectional method. The population in this study were all preclinical students of the Faculty of Medicine. The samples in this study were preclinical students from the class of 2015 with a sampling technique, namely the purposive sample technique. Primary data were obtained from questionnaires. Univariate analysis with frequency distribution analysis. The results of the study on students of the Faculty of Medicine from 180 respondents there were 23 people (13%), normal weight 112 people (62%), pre-obesity 33 people (18%), obesity as many as seven people (4%), and obesity II as many as five people (3%). Students who were pre-obese, obese I, and obese II were doing light activities as many as 15 people, 20 people doing moderate activities, and ten people doing strenuous activities. Students who have pre-obesity, obesity I, and obesity II are known as many as 20 people rarely consume fast food, and as many as 25 people often consume fast food. Abstrak: Tujuan penelitian ini dilakukan untuk mengetahui gambaran pola makan dan aktivitas fisik pada mahasiswa Fakultas Kedokteran yang berhubungan dengan obesitas. Jenis penelitian ini adalah penelitian deskritif dengan metode cross-sectional. Populasi dalam penelitian ini adalah semua mahasiswa/i preklinik Fakultas Kedokteran. Yang menjadi sampel pada penelitian ini adalah mahasiswa/i preklinik angkatan 2015 dengan teknik sampel yaitu teknik purposive sample. Data primer didapatkan dari kuesioner. Analisis univariat dengan analisis distribusi frekuensi. Hasil penelitian pada mahasiswa Fakultas Kedokteran dari 180 responden terdapat yang mengalami berat badan kurang sebanyak 23 orang (13%), berat badan normal sebanyak 112 orang (62%), pra obesitas sebanyak 33 orang (18%), obesitas I sebanyak 7 orang (4%), dan obesitas II sebanyak 5 orang (3%). Mahasiswa yang mengalami pra obes, obesitas I, dan obesitas II didapatkan yang melakukan aktivitas ringan sebanyak 15 orang, aktivitas sedang sebanyak 20 orang, dan yang melakukan aktivitas berat sebanyak 10 orang. Mahasiswa yang mengalami pra obes, obesitas I, dan obesitas II diketahui sebanyak 20 orang jarang mengkonsumsi fastfood , dan sebanyak 25 orang sering mengkonsumsi fast food.